Pathogenesis and treatment of cytokine storm in COVID-19 - (:unkn) unknown (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2022)
COVID-19 is a viral infection caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that killed a large number of patients around the world. A hyperinflammatory state resulting in a cytokine storm and adult respiratory distress syndrome seems to be the major cause of the death. Many mechanisms have been suggested in the pathogenesis of COVID-19 associated cytokine storm (COVID-CS). Insufficient viral clearance and persistence of a strong cytokine response despite inadequate antiviral immunity seem to be the main mechanisms underlying the pathogenesis. The diagnosis of COVID-19 is based on relatively constant clinical symptoms, clinical findings, laboratory tests, and imaging techniques, while the diagnosis of COVID-CS is a rather dynamic process, based on evolving or newly emerging findings during the clinical course. Management of COVID-19 consists of using antiviral agents to inhibit SARS-CoV-2 replication and treating potential complications including the cytokine storm together with general supportive measures. COVID-CS may be treated using appropriate immunosuppressive and immunomodulatory drugs that reduce the level of inappropriate systemic inflammation, which has the potential to cause organ damage. Currently corticosteroids, IL-6 blockers, or IL-1 blockers are most widely used for treating COVID-CS.
Keywords: COVID-19; SARS-CoV-2; cytokine storm; acute respiratory distress syndrome; tocilizumab; anakinra; EPIDEMIOLOGY; INFLAMMATION; ANAKINRA; EFFICACY; TNF